Analysis of the Use of TikTok Filter Bubble to Increase Content Engagement on Clipper Accounts: Analisis Pemanfaatan Filter Bubble TikTok untuk Meningkatkan Engagement Konten pada Akun Clipper - Ilham Muhammad; Khaerudin Imawan; Yanto Heryanto (Universitas Muhammadiyah Sidoarjo, 2026)
This study aims to analyze the utilization of the Filter Bubble phenomenon on TikTok to increase content engagement on Clipper accounts. TikTok uses a personalization-based recommendation system through the For You Page (FYP), which distributes content according to user interests, interaction history, and viewing behavior. In this study, Filter Bubble is examined through three analytical dimensions: information personalization, algorithmic curation, and selective exposure. The research employed a descriptive qualitative method. Data were collected through interviews, virtual observation, and documentation of five Clipper accounts, with @Juaaan as the main informant and @mugniXD, @SuperstarJumbo, @futuregrow.id, and @traeditz98 as supporting informants. The findings show that Clipper accounts utilize trending topics, distinctive editing styles, and content repackaging strategies to increase views, likes, comments, shares, and audience retention. The TikTok algorithm then strengthens the distribution of highly interactive content, creating repeated exposure to similar topics and sustaining engagement growth. This study confirms that Filter Bubble can be understood not only as a risk in digital communication, but also as a strategic opportunity for content visibility when applied ethically, creatively, and systematically.